2020
DOI: 10.1002/aoc.5611
|View full text |Cite
|
Sign up to set email alerts
|

Cu(I)‐anchored polyvinyl alcohol coated‐magnetic nanoparticles as heterogeneous nanocatalyst in Ullmann‐type C–N coupling reactions

Abstract: In this paper, the preparation of a novel magnetic nanocatalyst (Fe3O4@PVA/CuCl) is described, which involves coating of polyvinyl alcohol (PVA) onto the surface of Fe3O4 nanoparticles and its subsequent coordination with CuCl catalyst. The nanocatalyst was characterized by various analytical methods, including Fourier‐transform infrared, X‐ray diffraction, inductively coupled plasma spectroscopy, field emission scanning electron microscopy, energy‐dispersive X‐ray spectroscopy (EDX), transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 84 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…To explore the heterogeneity of the PSAPA⋅Cu(II) catalyst, the catalyst was filtered off while hot at 1 h when the arylated product yield was 22% [26] . K 2 CO 3 was added to the filtrate and the mixture was reacted for another 47 h. The solid catalyst removal significantly deteriorated the catalytic process afterwards, and only a slight yield increase to 41 % was noted, while that of the normal catalysis was 99 %.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the heterogeneity of the PSAPA⋅Cu(II) catalyst, the catalyst was filtered off while hot at 1 h when the arylated product yield was 22% [26] . K 2 CO 3 was added to the filtrate and the mixture was reacted for another 47 h. The solid catalyst removal significantly deteriorated the catalytic process afterwards, and only a slight yield increase to 41 % was noted, while that of the normal catalysis was 99 %.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of Fe 3 O 4 @PVA/CuCl. Reprinted with permission from ref Hemmati et al [ 163 ] Copyright 2020 John Wiley and Sons…”
Section: Copper Nanocatalystsmentioning
confidence: 99%
“…In the same year, Maleki and co-workers [162] demonstrated that CTSN/Fe 3 O 4 -Cu nanocomposite could be used as an inexpensive magnetic nanocatalyst for the N-arylation of imidazoles. This nanocatalyst was synthesized by dropwise addition of copper (II) acetate aqueous solution to a dispersed aqueous mixture of chitosan/Fe 3 O 4 and subsequent sonication for 1 h, at 80 C. [163] Copyright 2020 John Wiley and Sons S C H E M E 3 3 Ullmann cross-coupling reactions catalyzed by Fe 3 O 4 @PVA/CuCl…”
Section: S C H E M E 2 6 C-n Coupling Of Various Aryl Halides With Am...mentioning
confidence: 99%
See 1 more Smart Citation
“…Coupling reaction has emerged as a powerful tool to access carbon‐carbon and carbon‐heteroatom bonds [1,2,3] . Transition‐metal‐catalyzed coupling reactions have achieved rapid progress in recent times.…”
Section: Introductionmentioning
confidence: 99%